Assessing Freeman’s Stakeholder Theory - Stieb, James A. (Journal of business ethics, 2009)
At least since the publication of the monumental Strategic Management: A Stakeholder Approach (1984), the “stakeholder theory” originated by R. E. Freeman has engrossed much of the business ethics literature. Subsequently, some advocates have moved a bit too quickly and without proper definition or argument. They have exceeded Freeman’s intentions which are more libertarian and free-market than is often thought. This essay focuses on the versions of stakeholder theory directly authored or coauthored by Freeman in an effort to recover (1) Freeman’s intentions and (2) the argumentative justification of stakeholder theory. It then argues that Freeman’s appeal to legal, economic, and ethical constraints ultimately produce arguments that are invalid. One can thoroughly support legislation constraining corporations or seeking to prevent age discrimination, market monopolies, and externalities and regret the extent that capitalism is heir to such shortcomings without it following that (1) business beneficiaries should be changed from stockholders to stakeholders and (2) the latter should be given serious decision-making power. Further, stakeholder theory neither defines nor battles any obvious opposition. Hence, it is difficult to see what it changes about business management. In short, stakeholder theory either changes too much about business, or nothing important at all (depending on one’s interpretation). Efforts to supplant or improve the reigning theory of capitalism will have to do better.